Sperm divergence in a passerine contact zone: Indication of reinforcement at the gametic level - Albrecht, Tomáš; Opletalová, Kamila; Reif, Jiří; Janoušek, Václav; Piálek, Lubomír; Cramer, Emily R A; Johnsen, Arild; Reifová, Radka (Evolution; international journal of organic evolution, 2019)
Postcopulatory sexual selection may promote evolutionary diversification in sperm form, but the contribution of between-species divergence in sperm morphology to the origin of reproductive isolation and speciation remains little understood. To assess the possible role of sperm diversification in reproductive isolation, we studied sperm morphology in two closely related bird species, the common nightingale (Luscinia megarhynchos) and the thrush nightingale (Luscinia luscinia), that hybridize in a secondary contact zone spanning Central and Eastern Europe. We found: (1) striking divergence between the species in total sperm length, accompanied by a difference in the length of the mitochondrial sperm component; (2) greater divergence between species in sperm morphology in sympatry than in allopatry, with evidence for character displacement in sperm head length detected in L. megarhynchos; (3) interspecific hybrids showing sperm with a length intermediate between the parental species, but no evidence for decreased sperm quality (the proportion of abnormal spermatozoa in ejaculates). Our results demonstrate that divergence in sperm morphology between the two nightingale species does not result in intrinsic postzygotic isolation, but may contribute to postcopulatory prezygotic isolation. This isolation could be strengthened in sympatry by reinforcement.
Keywords: Germ Cells; genotyp; sexuální chování zvířat; lidé; Genotype; sperm size; Luscinia; zvířata; Humans; nightingales; zárodečné buňky; Species Specificity; Hybridization, Genetic; Passeriformes; hybridizace genetická; druhová specificita; Avian hybrid zone; Sexual Behavior, Animal; speciation; Animals